The effect of long term thermal exposure on plastics and elastomers - McKeen, Laurence W. (PDL handbook series, 2014)
Brings together a wide range of essential data on the effect of long term thermal exposure on plastics and elastomers, enabling engineers to make optimal material choices and design decisions